Pericyte loss influences Alzheimer-like neurodegeneration in mice - Sagare, Abhay P. (Nature Pub. Group, 2013)
Pericytes are cells in the blood–brain barrier that degenerate in Alzheimer’s disease (AD), a neurological disorder associated with neurovascular dysfunction, abnormal elevation of amyloid β-peptide (Aβ), tau pathology and neuronal loss. Whether pericyte degeneration can influence AD-like neurodegeneration and contribute to disease pathogenesis remains, however, unknown. Here we show that in mice overexpressing Aβ-precursor protein, pericyte loss elevates brain Aβ40 and Aβ42 levels and accelerates amyloid angiopathy and cerebral β-amyloidosis by diminishing clearance of soluble Aβ40 and Aβ42 from brain interstitial fluid prior to Aβ deposition. We further show that pericyte deficiency leads to the development of tau pathology and an early neuronal loss that is normally absent in Aβ-precursor protein transgenic mice, resulting in cognitive decline. Our data suggest that pericytes control multiple steps of AD-like neurodegeneration pathogenic cascade in Aβ-precursor protein-overexpressing mice. Therefore, pericytes may represent a novel therapeutic target to modify disease progression in AD.